Small‐Molecular‐Weight Additives Modulate Calcification by Interacting with Prenucleation Clusters on the Molecular Level. (29th July 2022) - Duchstein, Patrick; Schodder, Philipp I.; Leupold, Simon; Dao, Thi Q. N.; Kababya, Shifi; Cicconi, Maria R.; de Ligny, Dominique; Pipich, Vitaliy; Eike, David; Schmidt, Asher; Zahn, Dirk; Wolf, Stephan E.
Abstract: Small‐molecular‐weight (MW) additives can strongly impact amorphous calcium carbonate (ACC), playing an elusive role in biogenic, geologic, and industrial calcification. Here, we present molecular mechanisms by which these additives regulate stability and composition of both CaCO3 solutions and solid ACC. Potent antiscalants inhibit ACC precipitation by interacting with prenucleation clusters (PNCs); they specifically trigger and integrate into PNCs or feed PNC growth actively. Only PNC‐interacting additives are traceable in ACC, considerably stabilizing it against crystallization. The selective incorporation of potent additives in PNCs is a reliable chemical label that provides conclusive chemical evidence that ACC is a molecular PNC‐derived precipitate. Our results reveal additive‐cluster interactions beyond established mechanistic conceptions. They reassess the role of small‐MW molecules in crystallization and biomineralization while breaking grounds for new sustainable antiscalants. Abstract : Small but effective: only few small additives are potent antiscalants, extremely solubilizing CaCO3 . These underlying molecular mechanisms act beyond standard concepts of nucleation inhibition: they trigger, stabilize, and feed PNCs, presetting key properties of amorphous calcium carbonate (ACC). This study reveals how small molecules may co‐regulate biomineralization and breaks grounds for sustainable antiscalants.